2013
DOI: 10.1128/jvi.00240-13
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of In Vivo Defective Interfering-Like RNA of Influenza A H1N1 Pandemic Virus

Abstract: n Influenza virus defective interfering (DI) particles are naturally occurring noninfectious virions typically generated during in vitro serial passages in cell culture of the virus at a high multiplicity of infection. DI particles are recognized for the role they play in inhibiting viral replication and for the impact they have on the production of infectious virions. To date, influenza virus DI particles have been reported primarily as a phenomenon of cell culture and in experimentally infected embryonated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
181
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(225 citation statements)
references
References 38 publications
(58 reference statements)
23
181
1
1
Order By: Relevance
“…The quantitative levels of DIPs in natural samples have not been reported, but genome deletion DIPs may be present at levels of Ͻ10%, emphasizing the need for other quantification methods. Methods of detection of DIPs in natural populations include sequencing of promoters or other conserved sequences (8), but these have not provided quantitative population information. We have shown that differences in sequencing coverage for overlapping segments can reduce the effect of sequencing noise to provide more-quantitative estimates of population fractions and population changes during passaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative levels of DIPs in natural samples have not been reported, but genome deletion DIPs may be present at levels of Ͻ10%, emphasizing the need for other quantification methods. Methods of detection of DIPs in natural populations include sequencing of promoters or other conserved sequences (8), but these have not provided quantitative population information. We have shown that differences in sequencing coverage for overlapping segments can reduce the effect of sequencing noise to provide more-quantitative estimates of population fractions and population changes during passaging.…”
Section: Discussionmentioning
confidence: 99%
“…In nature, DIPs have been discovered in an outbreak of influenza A virus in chickens (5) and in West Nile virus isolates from avian hosts (6). In human hosts, clinical isolates from patients infected with dengue virus (7) and influenza A virus (8) provide evidence that DIPs and their genomes can be transmitted between patients.…”
mentioning
confidence: 99%
“…Defective interfering (DI) or other noninfectious influenza virus particles can be produced during the course of infection and can be detected by deep sequencing (50)(51)(52). To independently quantify the proportions of NAI-susceptible and -resistant influenza B viruses after coinfection of NHBE cells and to confirm the results of deep sequencing, we performed high-resolution melt (HRM) analysis (42) on individually purified plaques from 3 pairs of mixtures (rg-WT and either rg-E119A, rg-H274Y, or rg-R371K; example melt curves are shown in Fig.…”
Section: Inhibitory Activity Of Nais On Mixed Populations Of Nai-suscmentioning
confidence: 99%
“…To characterize the type of influenza virus-specific sequence reads that were removed from the RAW data set to obtain the RHM data set, all quality-controlled but unmapped and clipped reads were split in half, and both parts were remapped against their samplespecific consensus sequence. Defective influenza virus RNA was defined when the difference in starting mapping positions of both read parts was greater than the length of the read (29).…”
Section: Illumina Sequencing (I) Genome Analyzer Iix (Gaiix)mentioning
confidence: 99%